Enlarged uterus through a natural orifice: worth an effort? A randomized controlled trial - Mittal, Pratima; Andiliya, Amreesh; Bansiwal, Reeta; Suri, Jyotsna; Singal, Sunita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The objective was to compare the efficacy, safety and patient satisfaction of the Non-Descent Vaginal Hysterectomy (NDVH) with Total Abdominal Hysterectomy (TAH) in benign enlarged uterus. Methods: This was a prospective Randomized comparative study. A total of 60 subjects were randomly divided into VH and TAH groups (Group A, group B), by sealed opaque envelope, each comprising 30 subjects. Subjects having uterus of more than 12 weeks size requiring hysterectomy for benign pathology and non-prolapsed uterus were included in the study. Corporal bisection, morcellation, myomectomy, coring and combination of these were used as debulking procedures. Results: We could do all the VH successfully with no conversion to laparotomy and 100% success rate. The mean uterine size was 420.00 g ± 117.24 in group A and 454.33 g ± 52.50 in group B, mean operative time taken was more in group B as compared to group A, though not statistically significant (97 ± 4.46 min, 100 ± 7.27 min; P = 0.621).The mean blood loss, haemoglobin decrease and the Blood Transfusion was significantly lesser in VH group as compare to TAH group (251.13 ± 57.98 ml, 327.33 ± 58.54 ml; P = 0.000). There was no visceral injury in either group, though postoperative fever and wound infection were more in the TAH group than VH group. Conclusions: VH is safe and should be offered as the first surgical choice in women with uterine enlargement due to benign reasons and non-prolapsed uterus where feasible, and should be included in training program for residents and postgraduates trainees. It is definitely a surgical challenge worth the effort.